Effect of the solvent molar ratios on the synthesis of zeolitic imidazolate framework 8 (ZIF-8) and its performance in CO2 adsorption - Lai, L.S. (Trans Tech Publications Ltd, 2014)
In this research work, ZIF-8 was synthesized at room temperature using different synthesis solutions contained different molar ratios of methanol to zinc nitrate. The properties of the resultant particles were characterized using X-ray diffraction (XRD), transmission electron microscopy (TEM) and thermal gravimetric analysis (TGA). The basicity of the ZIF-8 samples was measured using temperature programmed desorption (TPD). Results showed that ZIF-8 samples synthesized in the present work were thermally stable up to 700 ÂºC. ZIF-8 synthesized using synthesis solution contained lowest molar ratio of methanol to zinc nitrate of 86.7 possessed highest crystallinity and largest average particles sizes of ~250 nm. Besides, this sample also demonstrated highest CO2 uptake rate due to the presence of highest amount of basic site of 0.70 mmol/g among the ZIF-8 samples. Â© 2014 Trans Tech Publications, Switzerland.